PENGARUH OBJEKTIVITAS, TANGGUNG JAWAB DAN PENGALAMAN AUDITOR TERHADAP EFEKTIVITAS AUDIT INTERNAL - Yuni Rachmawati; Firmansyah Arifin (Universitas Tridinanti, 2022)
This study aims to examine the effect of objectivity, responsibility and auditor experience on the effectiveness of internal audit. This study uses primary data in the form of questionnaires distributed to all SOE internal auditors in Palembang City. The number of samples collected and filled in completely according to the time limit was 34 respondents. This study uses the Structural Equation Model (SEM) Partial Least Square (PLS) approach using SmartPLS software. The results showed that the auditor's responsibility and experience variables had a positive effect on, while objectivity had no effect on the effectiveness of internal audits.Keywords: internal audit, objectivity, auditor experience, effectiveness